Comparison between ciprofloxacine and antibiotics of other pharmacological groups for urinary tract infection treatment - Arias Porras, José (2016)
Introduction. Urinary tract infections are a common reason of consultation in medical practical in ambulatory and emergency rooms in centers of health.  The inadequate and irrational use of antibiotics can favor the appearance of resistant bacterial strain and limit the capacity of response of these medicines.  This article seeks to review the use of quinolones (specifically ciprofloxacine) with antibiotics of other pharmacological groups and to compare efficiency and bacterial resistance.Method. From the methodology that indicates the clinical practice based on the evidence for the rapid reviews, there was established a clinical question to which response was tried to give by means of the search of primary investigations in electronic databases like MEDLINE, PubMed, Cochrane Library Plus and the Journal of Infection.Result. According to the type of bacterium and analyzed bacterial strain there is presence of resistance to diverse antibiotics. The infections of community origin have been treated by beta-lactamics, nitrofurantoine, trimetoprim-sulfametoxasol and fluoroquinolones (specially ciprofloxacine).Conclusion. It was not possible to determine if the quinolonas are more effective than the antibiotics that belong to other pharmacological groups.